2006
DOI: 10.1103/physrevb.73.085408
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory of surface-enhanced Raman scattering in noble-metal nanoparticles

Abstract: We present a microscopic model for surface-enhanced Raman scattering (SERS) from molecules adsorbed on small noble-metal nanoparticles. In the absence of direct overlap of molecular orbitals and electronic states in the metal, the main enhancement source is the strong electric field of the surface plasmon resonance in a nanoparticle acting on a molecule near the surface. In small particles, the electromagnetic enhancement is strongly modified by quantum-size effects. We show that, in nanometer-sized particles,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…While, within TDLDA, the Kohn-Sham wave functions are directly determined by the (self-consistent) confining potential, the local fields are, instead, defined solely by the induced charge density via the (screened) Coulomb potential and, therefore, depend on the confining potential indirectly. Hence, the deviation of E n from its classical behavior across the interface is determined by the electron density spillover over the classical (hard wall) boundary [73], and, therefore, is largely independent of the system overall shape. Furthermore, recent TDLDA studies of relatively large (up to 10 nm) nanoparticles revealed [55,56] that the main impact on plasmon linewidth comes precisely from the electron density tail and dielectric environment, implying that it is the plasmon local field near the interface, rather than electron wave functions, that chiefly determines the plasmon decay rate magnitude in real structures.…”
Section: Discussionmentioning
confidence: 99%
“…While, within TDLDA, the Kohn-Sham wave functions are directly determined by the (self-consistent) confining potential, the local fields are, instead, defined solely by the induced charge density via the (screened) Coulomb potential and, therefore, depend on the confining potential indirectly. Hence, the deviation of E n from its classical behavior across the interface is determined by the electron density spillover over the classical (hard wall) boundary [73], and, therefore, is largely independent of the system overall shape. Furthermore, recent TDLDA studies of relatively large (up to 10 nm) nanoparticles revealed [55,56] that the main impact on plasmon linewidth comes precisely from the electron density tail and dielectric environment, implying that it is the plasmon local field near the interface, rather than electron wave functions, that chiefly determines the plasmon decay rate magnitude in real structures.…”
Section: Discussionmentioning
confidence: 99%
“…Physically, the behavior illustrated in Fig. 1 can be understood as the result of electron spillover 31,32 (in the case of F-type boundary condition) or as the combined action of the finite charge density of the jellium and of the uncertainty principle (in the case of B-or R-type boundary conditions).…”
Section: Resultsmentioning
confidence: 99%
“…Now, SERS is playing an important role in surface science, spectroscopy, and detection [5] due to the high sensibility of detection with molecular identification capabilities [6,7]. It was believed that the mechanisms for the SERS enhancement include the chemical adsorption of the metal interface [8], quantum effects [9], and the electromagnetic (EM) field enhancement at the position of the single-molecule near metal nanoparticles [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%